2020
DOI: 10.3390/v12040386
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Lineage Variation of Lassa Virus Glycoprotein Epitopes: A Challenge to Lassa Virus Vaccine Development

Abstract: Lassa virus (LASV), which causes considerable morbidity and mortality annually, has a high genetic diversity across West Africa. LASV glycoprotein (GP) expresses this diversity, but most LASV vaccine candidates utilize only the Lineage IV LASV Josiah strain GP antigen as an immunogen and homologous challenge with Lineage IV LASV. In addition to the sequence variation amongst the LASV lineages, these lineages are also distinguished in their presentations. Inter-lineage variations within previously mapped B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 82 publications
2
34
0
4
Order By: Relevance
“…Most recently, the 10 th and 11 th glycans were reported to occlude the conformational GPC-B epitope located at the stalk of GPC (16). Notably, evidence from human survivor and vaccine development studies have shown that adaptive immune protection in LASV infection is probably conferred mainly by a cell-mediated immune response, especially for Type I IFN (9,(17)(18)(19)(20)(21)(22)(23). It was supposed that deletion of the glycan chain would expose the epitope and thus increase the immunogenicity of GPC.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the 10 th and 11 th glycans were reported to occlude the conformational GPC-B epitope located at the stalk of GPC (16). Notably, evidence from human survivor and vaccine development studies have shown that adaptive immune protection in LASV infection is probably conferred mainly by a cell-mediated immune response, especially for Type I IFN (9,(17)(18)(19)(20)(21)(22)(23). It was supposed that deletion of the glycan chain would expose the epitope and thus increase the immunogenicity of GPC.…”
Section: Discussionmentioning
confidence: 99%
“…2017 ; Warner et al . 2018 ; Ibukun 2020 ). It was supposed that deletion of the glycan chain would expose the epitope and thus increase the immunogenicity of GPC.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiology has so far revealed seven distinct lineages of the LASV, including four confirmed and three proposed lineages [ 20 24 ] suggesting localisation of infection around specific human-rodent communities and socioecology. Lineages I, II and III are found in Nigeria [ 22 ].…”
Section: Geographical Distribution Of Lassa Fevermentioning
confidence: 99%
“…Lineages II and III are common in southern and north-central Nigeria respectively [ 22 ]. Lineage IV, which includes the Josiah strain, comprises the subclades IVa and IVb, predominant in the Mano River Union area (Sierra Leone, Liberia and Guinea) [ 20 ]. In Sierra Leone, LF is endemic in the Eastern Province, particularly Kenema District [ 24 ], but has been reported in almost all districts of the country.…”
Section: Geographical Distribution Of Lassa Fevermentioning
confidence: 99%